Long-term comparison of everolimus- vs. novolimus-eluting bioresorbable vascular scaffolds in real world patients - Cakal, Beytullah; Cakal, Sinem; Karaca, Oguz; Omaygenc, Mehmet; Yilmaz, Filiz; Gunes, Haci; Ozcan, Ozgur; Yıldırım, Arzu; Boztosun, Bilal (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2020)
The largest amount of evidence for bioresorbable vascular scaffold (BVS) use in clinical practice derives from Absorb trials and registries. Comparison of Absorb BVS with metallic stents resulted in increased rates of target lesion failure and device thrombosis in the Absorb BVS group. We investigated whether all BVS platforms created equal outcomes. At 3-year follow-up novolimus-eluting BVS (Desolve Elixir Medical Corp., Sunnyvale, CA) achieved better outcomes compared with Absorb BVS. The scaffold thrombosis rate is still high with Absorb BVS despite pre- and post- dilatation. No scaffold thrombosis was present with Desolve BVS.